2011
DOI: 10.1080/08832323.2010.511303
|View full text |Cite
|
Sign up to set email alerts
|

Does Economics Education Make Bad Citizens? The Effect of Economics Education in Japan

Abstract: Does studying economics discourage students' cooperative mind? Several surveys conducted in the United States have concluded that the answer is yes. The authors conducted a series of economic experiments and questionnaires to consider the question in Japan. The results of the prisoner's dilemma experiment and public goods questionnaires showed no differences between the behaviors of economics majors and nonmajors. The uniqueness of economics majors was found in their answers to questions concerning whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Contrary to findings by Frank, Gilovich and Regan (1993), Seguino, Stevens and Lutz (1996), Frank and Schulze (2000), Hu and Liu (2003), Iida andOda, 2011, Gerlach (2017), and Kaiser et al (2018), we have not observed significant differences between decisions made by males and females. Furthermore, in our study women turned out to be less eager to contribute their resources to the common fund than their male counterparts.…”
Section: Discussion and Concluding Remarkscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to findings by Frank, Gilovich and Regan (1993), Seguino, Stevens and Lutz (1996), Frank and Schulze (2000), Hu and Liu (2003), Iida andOda, 2011, Gerlach (2017), and Kaiser et al (2018), we have not observed significant differences between decisions made by males and females. Furthermore, in our study women turned out to be less eager to contribute their resources to the common fund than their male counterparts.…”
Section: Discussion and Concluding Remarkscontrasting
confidence: 99%
“…This finding cast some doubt on whether economic education is a key determinant of students' performance in economic games. A similar conclusion came from an experiment that Iida and Oda (2011) conducted in Japan. Admittedly, the authors reported that Japanese students of economics cooperated less often in the Prisoner's Dilemma game than non-economists.…”
Section: Literature Reviewsupporting
confidence: 70%
“…The experimental results are sometimes contradictory or difficult to replicate (cf. Iida and Oda, 2011). The survey and experimental results and field data are occasionally difficult to compare and to evaluate, and they often do not complement each other very well.…”
Section: Discussionmentioning
confidence: 99%
“…The findings described above are difficult to add up to a consistent picture. Experimental results are sometimes contradictory or difficult to replicate (e.g., Iida & Oda, 2011). Survey and experimental results and real-world data are occasionally difficult to compare and to evaluate, and often do not complement each other very well.…”
Section: Discussionmentioning
confidence: 99%